Media slant against foreign owners: Downsizing - Guido Friebel; Matthias Heinz (Institute for the Study of Labor (IZA), 2012)
We establish the existence of strong media slant against foreign owners. Using a unique data set from nation-wide distributed quality newspapers in Germany, we find that a foreign firm that downsizes in Germany receives almost twice as much attention than a domestic firm. This quantitative slant is accompanied by qualitative slant; newspapers report in a more negative way about downsizing foreign than domestic firms. The slant is present in all quality newspapers, but it increases from right to left in the political spectrum. This is consistent with theory papers arguing that slant is an equilibrium phenomenon. The slant we document is a clean measure for economic xenophobia; however, not geared against migrants, but against foreign owners. The slant can be a substantial obstacle to FDI, as illustrated by case studies. Our results are likely to be a lower bound estimate, because Germans are rather globalization-friendly and we are looking at quality papers, not tabloids.
Keywords: L82; L33; L10; 330; media economics; globalization; economic xenophobia; multi-national enterprises; foreign direct investment; Personalabbau; Multinationales Unternehmen; Ausländisch; Mediale Berichterstattung; Standortfaktor; Ethnische Diskriminierung; Deutschland